Cabazitaxel versus abiraterone or enzalutamide in metastatic castration-resistant prostate cancer: post hoc analysis of the CARD study excluding chemohormonal therapy for castrate-naive disease. (19th March 2021) - Suzuki, Hiroyoshi; Castellano, Daniel; de Bono, Johann; Sternberg, Cora N; Fizazi, Karim; Tombal, Bertrand; Wülfing, Christian; Foster, Meredith C; Ozatilgan, Ayse; Geffriaud-Ricouard, Christine; de Wit, Ronald
Abstract: Background: In the CARD study (NCT02485691), cabazitaxel significantly improved clinical outcomes versus abiraterone or enzalutamide in patients with metastatic castration-resistant prostate cancer previously treated with docetaxel and the alternative androgen-signalling-targeted inhibitor. However, some patients received docetaxel or the prior alternative androgen-signalling-targeted inhibitor in the metastatic hormone-sensitive (mHSPC) setting. Therefore, the CARD results cannot be directly translated to a Japanese population. Methods: Patients ( N = 255) received cabazitaxel (25 mg/m 2 IV Q3W, prednisone, G-CSF) versus abiraterone (1000 mg PO, prednisone) or enzalutamide (160 mg PO) after prior docetaxel and progression ≤12 months on the alternative androgen-signalling-targeted inhibitor. Patients who received combination therapy for mHSPC were excluded ( n = 33) as docetaxel is not approved in this setting in Japan. Results: A total of 222 patients (median age 70 years) were included in this subanalysis. Median number of cycles was higher for cabazitaxel versus androgen-signalling-targeted inhibitors (7 versus 4). Clinical outcomes favoured cabazitaxel over abiraterone or enzalutamide including, radiographic progression-free survival (rPFS; median 8.2 versus 3.4 months; P < 0.0001), overall survival (OS; 13.9 versus 11.8 months; P = 0.0102), PFS (4.4 versus 2.7 months; P < 0.0001), confirmed prostate-specific antigen response (37.0 versus 14.4%; P = 0.0006) and objective tumour response (38.9 versus 11.4%; P = 0.0036). For cabazitaxel versus androgen-signalling-targeted inhibitor, grade ≥ 3 adverse events occurred in 55% versus 44% of patients, with adverse events leading to death on study in 2.7% versus 5.7%. Conclusions: Cabazitaxel significantly improved outcomes including rPFS and OS versus abiraterone or enzalutamide and are reflective of the Japanese patient population. Cabazitaxel should be considered the preferred treatment option over abiraterone or enzalutamide in this setting. Abstract : Cabazitaxel significantly improved radiographic progression-free survival and overall survival versus abiraterone or enzalutamide in patients who had not received combination therapy for metastatic hormone-sensitive prostate cancer. These data are reflective of a Japanese patient population.